Respuestas fisiológicas y morfológicas de cacao (Theobroma cacao L.) clon ccn 51 a la fertilización con diferentes fuentes de nitrógeno - Romero Zambrano, Melissa Alexandra (2019)
Cocoa (Theobroma cacao L.) is a crop in increasing demand. Although primary research dates back more than 40 years, the parameters for determining adequate fertilization are still unknown, and there is no clarity about the effects that the type of fertilizer will have on a physiological and productive level. Therefore, there is a need to evaluate the effects of nitrogen, one of the main and most widely used elements in cocoa. The objective of this research was to evaluate the physiological and morphological response of cocoa (Theobroma cacao L.) clone CCN 51 to the application of different nitrogen sources in fertilization (Urea, calcium nitrate and ammonium sulfate), considering a dose of 76.5 kg ha-1, based on the results obtained from an initial soil analysis. For this purpose, a field trial was carried out in the Piuntza neighborhood, Zamora canton, Zamora Chinchipe province, for a period of 5 months (November 2018 to March 2019), under a completely random design with 4 treatments and 10 repetitions. Within the measurements the following morphological variables were recorded monthly: bud length, bud TCA, bud TCR, length and number of metamers, leaf area of the bud, cob length, cob weight and ASTT. Macro and micronutrient analysis at foliar level, macronutrient analysis and soil pH were also performed, and the percentage of dry matter and crude fat of the cob was determined. As part of the results, until the end of the investigation the Witness at foliar and edaphic level presented lower concentrations of nitrogen, of 1.97 % and 84.83 ppm respectively, which indicates that the fertilizations were effective. The liming of the soil as part of the base fertilization increased the pH, while, when applying the treatments: Urea, Calcium Nitrate and Witness the pH gradually declined over time; however, when ammonium sulphate was applied, the soil pH was significantly reduced, returning to its initial value of 4.7. Urea fertilization increased soil K content by 0.56 meq 100 ml-1, while calcium nitrate and ammonium sulfate applications increased soil P content by 375.67 and 412.67 ppm respectively. In general, there were no statistically significant differences in the morphological variables evaluated. Keywords: Theobroma cacao L., nitrogen fertilization.